Analisis komparatif kinerja keuangan perbankan Syariah dan perbankan konvensional di Indonesia - Rofiqi, Alif Ahmad Sulthoni Putra (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the comparative financial performance between Islamic banking and conventional banking in Indonesia, focusing on two institutions: Bank Negara Indonesia (BNI) and Bank Syariah Indonesia (BSI). Since its introduction in 1983, Islamic banking has experienced significant development, especially after the launch of the National Action Plan for Islamic Banking in 2014. Descriptive analysis method was used to collect and compare financial data from both banks. The results showed that BNI has higher total assets and net income than BSI, with better ROA and ROE. However, BSI showed higher financing growth and remained efficient in asset utilization. This study highlights the importance of innovation and technological adaptation in improving the competitiveness of Islamic banking amidst the dominance of conventional banking. These findings provide insights for the development of strategies in the Islamic banking sector to improve their performance and competitiveness in an increasingly competitive market.